OTORITAS NABI MUHAMMAD SAW Kajian atas Peran dan Fungsi Hadis dalam Hukum Islam - Zulfahmi, Zulfahmi (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2019)
As a perfect religion, Islamic teachings present the concept that could cover all aspects of human’s life. One of the important aspect of Islamic teachings is about provision of Islamic law and its implementation in society. The Islamic law is binding on all Muslim’s conduct as an individual as well as a community. Nobody has the authority to modify or replace it with another law. On the other part, Allah sent Muhammad to all human kind as His Prophet and Mesengger. Allah purposely made the entire life of the Prophet of Muhammad, including his decision, consideration and commands, as law enforcement. Therefore, the prophet of Muhammad became a crucial figure in Islam as an interpreter of al Quran, a legislator, obeyed figure, and a role model in conducting and implementing the Islamic teaching.